Residual levels of imazamox herbicide and derivatives in different parts of sunflower plant and honey samples produced under the effect of sunflower flora - Ulviye ÇEBİ; Cemile ÖZCAN; Mehmet Ali GÜRBÜZ; Selçuk ÖZER (Derim, 2019)
This research was carried out under flowerpot conditions in Kırklareli province of Thrace region. The pots were filled with two different soil types, which had loamy sand and sand structures. The imazamox with the doses of 0.5 and 7.5 ml da-1 were applied to the sunflower plant when it had 4-10 leaves. The study was carried out in watery conditions and the irrigations were done three different phenological periods. Imazamox residual amounts were determined in leaf, stem and table parts of the sunflower plant in the study. Besides, the honey samples, which were produced under the effect of sunlower flora, were collected from different regions and it was investigated whether or not the imazamox herbicide left residual in the final products. According to the results, the imazamox residual amount levels in different parts of the plant were ranged as table>leaf>stem. Imazapic and imazapyr derivatives in the leaf part and imazapic derivatives in the stem part were observed. Different amounts of imazamox doses, irrigation ratios and the soil structure were effective on the residual amounts. The residuals of imazamox and derivatives in the honey samples were not observed.